Safe Use of Sodium Dodecyl Sulfate (SDS) to Deactivate SARS-CoV-2: An Evidence-Based Systematic Review - Kumar, Ashok; Ansari, Waseem A.; Ahamad, Tanveer; Saquib, Mohammad; Khan, Mohammad Faheem (Coronaviruses, 2021)
Background: Coronavirus disease (COVID-19) has now morphed into the most serious healthcare challenge that the world has faced in a century. The coronavirus disease (COVID-19) was declared as a public health emergency of international concern (PHEIC) on January 30, 2020, and a pandemic on March 11 by the World Health Organization (WHO). The number of cases and the death toll are rapidly increasing frequently because of its fast transmission from human to human through droplets, contaminated hands or body, and inanimate surfaces. Objective: SDS has been found to exhibit broad-spectrum and effective microbicidal and viral inactivation agents through the denaturation of both envelope and non-envelop proteins Methods: Viable SARS-COV-2 particles may also be found on contaminated sites such as steel surfaces, plastic surfaces, stainless steel, cardboard, and glass surfaces that can serve as a source of virus transmission. We reviewed the available literature about the SARS-CoV-2 persistence on inanimate surfaces as well as the decontamination strategies of corona and other viruses by using Sodium dodecyl sulfate (SDS) as well as other cleaning chemicals and disinfectants. Results: The efficacy of SDS has been amply demonstrated in several studies involving human immunodeficiency virus (HIV), human papillomavirus (HPV) and herpes simplex virus (HSV). SDS has also been found as deactivator of SARS-CoV-2. In toxic profile, up to 1% concentration of SDS is safe for humans and showed no toxic effect if ingested. Conclusion: Since no specific treatment is available as yet so containment and prevention continue to be important strategies against COVID-19. In this context, SDS can be an effective chemical disinfectant to slow and stop the further transmissions and spread of COVID-19.
Keywords: COVID-19